SAT0098 The association between work disability and mental health in rheumatoid arthritis. (15th June 2017) - Houssien, A; Norton, S; Nikiphorou, E; Matcham, F; Galloway, J
Abstract : Background: Rheumatoid arthritis (RA) is characterised by joint inflammation, resulting in functional impairment. Consequently, it has long been recognised that work disability is common in RA. However, despite significant pharmacological advances in disease control, little is known about contemporary impact upon work. Depression has emerged in recent years as a key comorbidity in RA. In the general population, depression is strongly correlated with work disability Objectives: To establish the extent to which depression associates with work ability in RA in a cross sectional study. Methods: Our hospital routinely collects data via an electronic screening interface, which incorporates a series of validated questionnaires, which patients complete via an iPad while waiting for their appointment. The dataset is linked to the clinical record. For this study, cross sectional data were extracted on adults with RA. Question 2 of the Work and Social Adjustment Scale ("Because of my [RA] my ability to work is impaired") was used as a measure or work disability (scale 0–8). Mental health status was collected using the Patient Health Questionnaire-2 (PHQ), with a score≥3 considered a positive screen for depression. Results: Of 385 patients with RA were included in the analysis. Their demographics are shown in the Table.1 Patients scoring 3 or more on the PHQ had more severe RA (higher DAS/HAQ), but there was no significant difference in age, sex or disease duration. 124 (32%) reported no work disability, with the overall mean score 3.0. Patients screening positive for depression had a significantly lower work ability even after adjusting for available confounders. Conclusions: There is a significant correlation between depression in RA and work ability, which persists even after accounting for disease severity. The magnitude of association observed was even greater than that seen between physical function and work. Although unmeasured confounding remains likely, these data confirm the link between depression and work in RA. It is likely that the relationship is bidirectional, between depression and work in RA. Beyond the importance of addressing work ability in RA, the results highlight the need for screening and targeting depression as part of routine clinical care beside the holistic approach of mangement. Disclosure of Interest: None declared